Addressing Anti‐Black Racism in Bioethics: Responding to the Call. (26th April 2022) - Fletcher, Faith E.; Ray, Keisha S.; Brown, Virginia A.; Smith, Patrick T.
Abstract: As a field concerned with ethical issues in health and health care, particularly how structures, policies, and practices unfairly advantage some and disadvantage others, bioethics has a moral obligation to address the long‐standing challenges that racism has posed to the overall health and well‐being of Black, Indigenous, and Latinx people and other people of color. Arguably, the premature death and disease disproportionately affecting Black Americans and the well‐documented association of such death and illness with racism are issues that have not gained due attention in bioethics. This multiauthored report highlights the intergenerational work of mostly Black scholars and aims to create an agenda for bioethics that addresses anti‐Black racism and the ways in which this form of racism threatens the actualization of justice in health and health care, not only for Black people and other minoritized groups but also for all people. This special report contains five major sections representing different approaches to scholarship, including theoretical, empirical, and narrative forms. The first section features two target articles focused on anti‐Black racism and health care settings, with each article accompanied by two commentaries. The second section includes four essays thematically centered around anti‐Black racism and health equity research and practice. Section three features four essays that explore anti‐Black racism and bioethics. The next section consists of four essays framing a braver, bolder, and broader bioethics. We conclude with a powerful tribute to the late Marian Gray Secundy, a bioethics luminary, friend, colleague, role model, and mentor, and a tie that binds together many bioethics scholars who prioritize social justice in their scholarship and praxis.